Reframing School Culture through Project-Based Assessment Tasks: Cultivating Transformative Agency and Humanizing Practices in NYC Public Schools. Issue 4 (April 2021) - Hantzopoulos, Maria; Rivera-Mccutchen, Rosa L.; Tyner-Mullings, Alia R.
Background/Context: In the last two decades, high-stakes testing policies have proliferated exponentially, radically altering the broader educational landscape in the United States. Although these policies continue to dominate educational reform agendas, researchers argue that they have not improved educational outcomes for youth and have exacerbated inequities in schooling across racial, economic, geographic, and linguistic lines. Alternative project-based assessments, like ones used by the New York Performance Standards Consortium (Consortium) are one type of practice to have shown promise in aiding in the creation of humanizing and transformative educational spaces. Purpose/Objective/Research Question/Focus of Study: This article examines how teachers and students make meaning of their experiences transitioning away from high-stakes standardized tests to project-based assessment tasks (PBATs) and specifically considers the role that PBATs might play in shaping school culture. Drawing from three years of data collection at 10 New York City public high schools new to the Consortium, we discern how students and teachers negotiate this shift, paying attention to the ways in which PBATs fostered transformative and humanizing pedagogies and practices. We raise the following questions: How can schools that use project-based assessment reinvigorate school culture to address enduring inequities that persist in schools? How might PBATs reframe schools to be more humanizing and transformative spaces? Research Design: We used multiple methods to understand how project-based assessment shapes school culture and curriculum in these transitioning schools, and drew from qualitative and quantitative traditions. The research involved: (1) a historical inquiry into the role of the Consortium in school reform; (2) a broad investigation of the 10 schools transitioning into the Consortium (including three rounds of annual surveys with teachers and administrators); (3) three in-depth focal case studies of transitioning schools (including observations, interviews with teachers, and surveys with students); and (4) surveys with experienced teachers new to established Consortium schools. Conclusions: PBATs are a useful tool to engage students and teachers more actively as participatory actors in the school environment, particularly when overall school structures collectively support its integration. Although there were inevitable challenges in the process of transition, our data suggest that the school actors mediated some of these tensions and ultimately felt that PBATs helped create more dignified spaces for youth. By anchoring the assessment process in the concept of transformative agency, we consider how the transition to PBATs might reinvigorate school culture, redress harmful systemic injustices, and serve as a necessary part of school reform and education policy.